Climate-oriented assessment of main street design and development in Budapest. Issue 4 (1st October 2016) - Csete, Maria; Buzasi, Attila
Abstract: Main streets play pivotal role in urban areas in terms of economic, social, moreover environmental contexts. Such streets are generally situated in densely built-up areas, where the adverse effects of climate change, such as rising temperature and changing precipitation patterns occur emphatically. Increasing urban heat island effect or extreme amount of runoff water during severe storms and floods significantly decrease the adaptive capacity of a city, consequently its residents becoming more vulnerable. Therefore involving climate-oriented design principles into planning and construction phase contributes to reach more sustainable and climate-friendly open spaces what are strongly relevant especially in main streets which are designed for a great amount of people. Present study provides a criteria matrix for assessing the climate-friendly level of recently renewed main streets in Budapest. Due to this assessment tool the adaptation and mitigation performance of the selected projects can be evaluated. For identifying strengths and weaknesses of a given project, a rating scheme has been applied by selecting and using 42 indicators grouped into mitigation, adaptation and awareness raising categories. Thus planners, decision-makers and other stakeholders can easily define future opportunities and challenges, accordingly this study may contribute to take urban street design practices toward climate-friendliness by paying more attention on changing local weather patterns and related consequences.